Opieka nad chorymi jako droga do świętości według św. Doroteusza z Gazy - Turzyński, Piotr (Vox Patrum, 2018)
The article presents a part of spirituality of Saint Dorotheus of Gaza, the Palestinian monk and abbot from VI century. He wrote instructions and letters for monks in which one of the topics is also care for the sick. Dorotheus himself before became an Abba was educated in medicine and in monastery was responsible for infirmary. He underlines that after first step on the road of improvement which is purification man must fill his heart with good deeds. Care for the sick is one of them. Dorotheus is looking on disease in the light of Divine Providence. In this way the disease is a trial, but also body sickness could be medicine for the soul. If someone is looking after the sick he has an opportunity to learn humility and wisdom of life. Dorotheus invites monks to do this disinterestedly. By that means sickness becomes a way to holiness.